Pancreatic cancer outcome—local treatment with radiation using MRI-LINAC - Almog, Galit; Pfeffer, Raphael M.; Zalmanov, Svetlana; Grinberg, Vladislav; Lipsky, Yoav; Chernomordikov, Elena; Levin, Daphne; Apter, Sara; Arsenault, Orit; Epstein, Dan; Tamimi, Qusai; Hod, Keren; et al. (Frontiers in Oncology, 2023)
No patient reported grade ≥2 acute GI toxicity. All previously irradiated patients reported only low-grade toxicities during RT. Forty-eight patients (88.9%) were available for evaluation. Complete local control was achieved in 21.7% (10 patients) for a median of 9 months (2.8-28.8), three had later local progression. Eight patients had regional or marginal recurrence. Six-month and 12-month OS were 75.0% and 52.1%, respectively. Apart from mild diarrhea 1-3 months after SMART and general fatigue, there were no significant differences in toxicity and outcomes between post-pancreatectomy and inoperable groups.SMART allows safe delivery of an ablative dose of radiotherapy, with minimal treatment-related toxicity, even in previously resected or irradiated patients. In this real-world cohort, local control with complete response was achieved by 20% of the patients. Further studies are needed to evaluate long-term outcome and late toxicity.